2019
DOI: 10.1136/bmjgh-2019-001453
|View full text |Cite
|
Sign up to set email alerts
|

Primary healthcare policy and governance in low-income and middle-income countries: an evidence gap map

Abstract: IntroductionGovernance is one of the most important aspects for strong primary healthcare (PHC) service delivery. To achieve the targets for the Sustainable Development Goals, good governance may play a prime role in low-income and middle-income countries (LMICs). This evidence gap map (EGM) explored the available evidence in LMICs to identify the knowledge gap concerning PHC policy and governance in these settings.MethodsWe followed the standard 3ie EGM protocol, finalising the scope of the EGM through a stak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…139,140 Multiple studies reported that intersectoral collaboration combined with community engagement among all health care stakeholders of LMICs improves healthcare indices and access to healthcare in these countries. [141][142][143] PHC Enhances Community Participation Community participation or engagement, another principal strength of PHC, has been reported as being highly influential on the prevention and control of NCDs. 144 Community participation is described as a method and practice by which ordinary people and societies are empowered to be involved dynamically and meaningfully in identifying and describing the health-issues concerning themselves.…”
Section: Strengths Of Primary Health Carementioning
confidence: 99%
“…139,140 Multiple studies reported that intersectoral collaboration combined with community engagement among all health care stakeholders of LMICs improves healthcare indices and access to healthcare in these countries. [141][142][143] PHC Enhances Community Participation Community participation or engagement, another principal strength of PHC, has been reported as being highly influential on the prevention and control of NCDs. 144 Community participation is described as a method and practice by which ordinary people and societies are empowered to be involved dynamically and meaningfully in identifying and describing the health-issues concerning themselves.…”
Section: Strengths Of Primary Health Carementioning
confidence: 99%
“…, 2019 ). In an ‘evidence gap map’ exploring the available evidence in LMICs concerning PHC policy and governance, Saif-Ur-Rahman et al. (2019) demonstrate that among the highest priority research areas are better governance in PHC, public–private partnerships for community leadership and accountability, and improved user–provider communication.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is challenging to reach the most marginalized groups particularly in a context of low coverage of social protection schemes like Bangladesh. Low coverage increases competition among applicants and thus holds greater risk for inequitable allocation of coverage based on nepotism, bribery, patronage and political gain [10,56]. Thus, there is a need for strong monitoring and supervision systems, and also strong political commitment to achieve the goal of each social protection scheme [10].…”
Section: Access Inequalitiesmentioning
confidence: 99%